Effectiveness of entrepreneurship policies: some evaluation research perspectives - Petra Tausl Prochazkova; Michaela Krechovska; Ladislav Lukas (Amfiteatru Economic)
Entrepreneurship has recently become a tremendous topic of discussion. Although at the centre of interest of every public policy there are obviously efforts to foster entrepreneurial ventures, there is still a gap in a possible methodology of measuring and monitoring the effectiveness of entrepreneurship support policies. The aim of this paper is to propose a possible methodology of the measurement such effectiveness of entrepreneurship policies. First, there are presented the most relevant facts on entrepreneurship, as well as entrepreneurship support policy as a prerequisite for entrepreneurship development. Suitable methods of measuring of the impact of entrepreneurship policies are discussed, which results in a proposal of own research methodology based upon AHP (Analytic Hierarchy Process). The research methodology is based on several indicators that are considered to be the most relevant elements to entrepreneurship outcomes in today’s economy. Indicators of a micro economic character and macro-economic character are chosen. The proposed methodology of evaluation of effectiveness of entrepreneurship policies is verified by means of a case study